The Role of Pontin and Reptin in Cellular Physiology and Cancer Etiology - Mao, Yu-Qian; Houry, Walid A. (Frontiers in Molecular Biosciences, 2017)
Pontin (RUVBL1, TIP49, TIP49a, Rvb1) and Reptin (RUVBL2, TIP48, TIP49b, Rvb2) are highly conserved ATPases of the AAA+ (ATPases Associated with various cellular Activities) superfamily and are involved in various cellular processes that are important for oncogenesis. First identified as being upregulated in hepatocellular carcinoma and colorectal cancer, their overexpression has since been shown in multiple cancer types such as breast, lung, gastric, esophageal, pancreatic, kidney, bladder as well as lymphatic and leukemic cancers. However, their exact functions are still quite unknown as they interact with many molecular complexes with vastly different downstream effectors. Within the nucleus, Pontin and Reptin participate in the TIP60 and INO80 complexes important for chromatin remodeling. Although not transcription factors themselves, Pontin and Reptin modulate the transcriptional activities of bona fide proto-oncogenes such as MYC and β-catenin. They associate with proteins involved in DNA damage repair such as PIKK complexes as well as with the core complex of Fanconi anemia pathway. They have also been shown to be important for cell cycle progression, being involved in assembly of telomerase, mitotic spindle, RNA polymerase II and snoRNP. When the two ATPases localize to the cytoplasm, they were reported to promote cancer cell invasion and metastasis. Due to their various roles in carcinogenesis, it is not surprising that Pontin and Reptin are proving to be important biomarkers for diagnosis and prognosis of various cancers. They are also current targets for the development of new therapeutic anticancer drugs.